Al-Amānah fī al-Ḥukm fī Ḍawʻ al-Qurʻān al-Karīm - Ahmaddin Ahmad Tohar (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2003)
Implementation of the law fairly is the pillar of Islamic teachings. Discrimination law enforcement based on the implementation of the social status or family ties is an injustice. Justice is the mandate of each individual. Al-Quran is the source of Islamic law that must be followed by every Muslim in establishing a law.